Interrogations for Solo Serge parts 1-4 - Koutsomichalis, Marinos (My University, 2026)
'Interrogations for Solo Serge parts 1-4' performed at Electroacoustic Music Days online festival, facilated by the Hellenic E/A Music Composers’ Association. http://www.essim.gr/meres2020/el/schedule.html